The impact of digital presence and use of information technology on business performance of veterinary practices: a case study of Bosnia and Herzegovina - Fejzić, Nihad; Muftić, Abdullah; Šerić-Haračić, Sabina; Muftić, Emina (Frontiers in Veterinary Science, 2023)
The veterinary profession is facing various challenges in the 21st century, such as livestock production intensification, shifting distribution of infectious diseases, growing focus on food safety alongside growing demand for companion animals’ veterinary services. Information technologies and digitalization trends had driven changes in many business sectors, including providing veterinary services thus opening new avenues to overcome the existing challenges this profession is facing. A study conducted among 244 veterinary practices in Bosnia and Herzegovina revealed that only 10.2% had a business-associated website, and 54.9% were present on at least one social media platform. The study suggests that a positive impact on annual profit can be achieved through the implementation of effective digital marketing strategies such as web presence, search engine optimization, Google business account existence, website Google advertisement, continuous administration of social media, and social media advertisement. The statistical analysis indicates that Google advertisements, website Search Engine Optimization, and social media advertisements greatly affect annual profit. Thus, improving digital presence of veterinary businesses with professionally managed websites, use of social media platforms, investment in online marketing strategies, and adopting telehealth services and online access to patient records positively affects business performance and better fits the growing needs of clients and society.